Consanguinity and Neural Tube Defects - Nuzhat Nauman , Shireen Rafiq , Samina Jalali , Sajjad AslamShami , Nadeem Akhtar (Journal of Rawalpindi Medical College, 2016)
Background: To determine the number of consanguineous unions in parents of children born with neural tube defects. Methods: For this case-control study 190 pregnant women coming for delivery/ termination to the Obstetrics Department, Holy Family Hospital, Rawalpindi, 2005-2007 affected with a Neural Tube pregnancy and 100 control mothers were directly interviewed and a specially structured performa was filled regarding demographic, reproductive and consanguinity data . Results: In this study 60 % of couples were consanguineous with a neural tube pregnancy as compared to 45% in controls. Of the 60%, there were 46.84 % first cousins. Neural tube defects included mostly anencephaly (18.95%), encephalocele (4.74%), meningocele (42.11%) and myelomeningocele(30%). Neural tube defects are multifactorial with genetic as well as environmental factors in its etiology. Majority (63.53%) were from rural areas. Majority of patients were illiterate or had limited education and mostly had low socioeconomic background. Neural Tube anomalies encountered were autosomal recessive with a risk of recurrence in subsequent pregnancies. Conclusion: There were significantly more consanguineous couples with a neural tube pregnancy as compared to controls. Genetic counseling could be beneficial for consanguineous couples. There is a need to educate the public on the possible harmful effects of inbreeding, especially in developing countries with high rates of consanguinity and limited financial resources